Beyond neoliberal and deconstructive space: horizō and infinity in the twenty-first century - Koljević Grifit, Bogdana (Sociološki pregled, 2025)
Beginning from reference to Lefebvre’s spatiology, in this article the author elaborates how political and social space disappeared in and with neoliberalism and postmodernity. Both discourses appear through the image of the Piraeus as the commercial city and therefore, in contrast to the city of Athens, the agora and polis proper. Real space, the representation of space as well as spaces of representation in these cases emerge as post-politics. In the second part, turning to twenty-first century’s perspective, horizō – as the act of division and separation – is presented as the first condition for recognition of otherness and difference and, further, for the creation of a multitude in opposition to totality. In order, however, for the transition from conflict to dialogue to occur, the concept of infinity is disclosed as necessary as the demand for justice from which existence in togetherness becomes possible. Finally, this is exemplified in Serb topoi as a potentiality of polis in contemporary Europe.